Chinesische Gärten im Kosmos: Die östliche Perspektive in Alexander von Humboldts Konzept des Ganzen der Natur - LONG, Qiyu (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
In his work, Alexander von Humboldt explores the natural expressions of different cultures, particularly praising the richness and diversity of Asian approaches. He highlights examples such as Qianlong’s Shengjing Fu and the Chengde Mountain Resort, viewing this royal garden as a unique fusion of nature and culture. It not only reflects the emperor's love for nature but also embodies the unity of human craftsmanship and pristine nature, serving as a microcosm of natural landscapes and a symbol of harmonious coexistence between humanity and the natural world. By examining China, Humboldt supports his concept of natural unity, enriching his physiognomy of nature, and offering new perspectives on the relationship between nature and culture on a global scale.